Light-Triggered Enantioselective Organocatalytic Mannich-Type Reaction - Hepburn, Hamish B.; Magagnano, Giandomenico; Melchiorre, Paolo (Synthesis, 2017)
Disclosed herein is a photochemical organocatalytic strategy for the direct enantioselective Mannich-type reaction of 2-alkylbenzophenones and cyclic imines. The chemistry exploits the light-triggered enolization of 2-alkylbenzophenones to generate transient hydroxy-o-quinodimethanes. These fleeting intermediates can be stereoselectively intercepted by imines upon activation with a chiral organic catalyst, derived from natural cinchona alkaloids. The developed method uses mild conditions, simple sources of illumination, and easily available substrates and catalysts, affording enantioenriched chiral amines that are difficult to synthesize by other approaches.
Keywords: enantioselective catalysis; organocatalysis; Mannich-type reaction; photochemistry; synthetic methods